PENGEMBANGAN BAHAN AJAR ELEKTRONIK BERBASIS FLIPBOOK UNTUK MENINGKATKAN HASIL BELAJAR IPA SEKOLAH DASAR - Faiza Alvi Millati; Novi Setyasto (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
The present study investigates the efficacy of flipbook-based electronic teaching materials as an alternative to traditional government-provided materials in elementary schools, which have been found to yield unsatisfactory learning outcomes. The study draws inspiration from the work of Borg and Gall and was conducted at Srondol Wetan 06 Public Elementary School, Semarang City, during the 2022/2023 school year. The study population consisted of 34 students, with a small-scale trial involving eight students in class VA, and a large-scale trial involving 26 students in class VB. Data collection methods included pre-test post-test assessments, observations, questionnaires, interviews, and data documentation. The results indicate high feasibility in terms of media aspect (83) and material criteria (69), with linguistic analysis yielding a feasibility score of 45. Furthermore, the effectiveness analysis showed a moderate N-gain score of 0.658, indicating improved learning outcomes, and student response questionnaires yielded a very positive score of 256. The result of t-test sig 0.000 there is a difference between pretest and posttest. These findings lead to the conclusion that flipbook-based electronic teaching materials are both feasible and effective for enhancing student learning outcomes in class V at SDN Srondol Wetan 06.